2022
DOI: 10.3390/genes13020347
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs Controlling Resistance to Anthracnose Disease in Water Yam (Dioscorea alata)

Abstract: Anthracnose disease caused by a fungus Colletotrichum gloeosporioides is the primary cause of yield loss in water yam (Dioscorea alata), the widely cultivated species of yam. Resistance to yam anthracnose disease (YAD) is a prime target in breeding initiatives to develop durable-resistant cultivars for sustainable management of the disease in water yam cultivation. This study aimed at tagging quantitative trait loci (QTL) for anthracnose disease resistance in a bi-parental mapping population of D. alata. Paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
5
1
Order By: Relevance
“…While previous studies identified two significant anthracnose QTL using EST-SSRs 25 and three QTL using GBS-SNPs 62 , none of these colocalize with the QTL in our study. This discrepancy (and the variability seen among different years in our work) may be due to differences in the parental yam genotypes, differences in anthracnose strain and/or inoculation rate in these field studies, and possible genotype-by-environment interactions.…”
Section: Resultscontrasting
confidence: 96%
“…While previous studies identified two significant anthracnose QTL using EST-SSRs 25 and three QTL using GBS-SNPs 62 , none of these colocalize with the QTL in our study. This discrepancy (and the variability seen among different years in our work) may be due to differences in the parental yam genotypes, differences in anthracnose strain and/or inoculation rate in these field studies, and possible genotype-by-environment interactions.…”
Section: Resultscontrasting
confidence: 96%
“…Such analysis has been employed in many crops (including yam) to explore the alleles for enhancing agronomic, flower sex and biotic stress tolerance. 14,23,[52][53][54][55]…”
Section: Discussionmentioning
confidence: 99%
“…The prediction for the lowest index value refers to the closeness to the ideal genotype and thus indicates the desired quality for BY/PY food product. Such analysis has been employed in many crops (including yam) to explore the alleles for enhancing agronomic, flower sex and biotic stress tolerance 14,23,52‐55 …”
Section: Discussionmentioning
confidence: 99%
“…• This study is a pioneer that validated kompetitive allele-specific (KASP)-based single nucleotide polymorphism (SNP) assay for quality control (QC) and assurance in yam breeding. Girma et al, 2014Girma et al, , 2015Loko et al, 2017;Siadjeu et al, 2018), evolution of yam domestication (Sugihara et al, 2020), quantitative trait locus identification (Agre et al, 2022;Bhattacharjee et al, 2018;Cormier, Lawac, et al, 2019), and genomic prediction (Norman et al, 2020). Routine breeding activities (assessment of genetic diversity or identification of mislabeled genotypes, pedigree verification, variety tracking, so on), also known as quality control (QC) in crop breeding leveraging molecular breeding tools, have been employed as a routine practice in many breeding and seed programs to harness genetic gain and delivery of quality products to the end users.…”
Section: Core Ideasmentioning
confidence: 99%